2022
DOI: 10.1007/s10698-022-09427-w
|View full text |Cite
|
Sign up to set email alerts
|

Improving student success in chemistry through cognitive science

Abstract: Chemistry educator Alex H. Johnstone is perhaps best known for his insight that chemistry is best explained using macroscopic, submicroscopic, and symbolic perspectives. But in his writings, he stressed a broader thesis, namely that teaching should be guided by scientific research on how the brain learns: cognitive science. Since Johnstone’s retirement, science’s understanding of learning has progressed rapidly. A surprising discovery has been when solving chemistry problems of any complexity, reasoning does n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Additionally, acid-base chemistry is ubiquitous throughout the undergraduate chemistry curriculum (van Kesteren et al, 2018), while conformations, which are essential to understanding the antiperiplanar relationship, are only introduced in organic chemistry (Scheme 1). The chemical education literature (Hartman et al, 2022) and our theoretical framework support the idea that students are more likely to utilize cognitive resources that have been repeatedly activated over time.…”
Section: Mechanisticsupporting
confidence: 54%
“…Additionally, acid-base chemistry is ubiquitous throughout the undergraduate chemistry curriculum (van Kesteren et al, 2018), while conformations, which are essential to understanding the antiperiplanar relationship, are only introduced in organic chemistry (Scheme 1). The chemical education literature (Hartman et al, 2022) and our theoretical framework support the idea that students are more likely to utilize cognitive resources that have been repeatedly activated over time.…”
Section: Mechanisticsupporting
confidence: 54%
“…Additionally, acid-base chemistry is ubiquitous throughout the undergraduate chemistry curriculum (van Kesteren et al, 2018), while conformations, which are essential to understanding the antiperiplanar relationship, are only introduced in organic chemistry. The chemical education literature (Hartman et al, 2022) and our theoretical framework support the fact that students are more likely to utilize cognitive resources that have been repeatedly activated over time. To complement the deficit-oriented deductive codes, we also employed an inductive coding strategy in which we generated codes based on the trends observed in the student responses to the survey assessment questions (Table 3).…”
Section: Q1: E2 Eliminationmentioning
confidence: 53%
“…In future iterations of the bootcamp, periodic review sessions on the bootcamp content throughout the first semester may strengthen the impact on mathematics competence. The bootcamp approach is most appropriate for students who have learned the bootcamp topics in previous courses . While students without this prerequisite knowledge may be best served by enrolling in the appropriate math coursework before enrolling in graduate physical chemistry coursework, these review sessions may facilitate the learning curve for all students.…”
Section: Future Workmentioning
confidence: 99%
“…Incoming graduate students have diverse backgrounds and hence could be impacted differently in the short- and long-term by a peer-led problem-solving practice. Recent work in the cognitive sciences has shown that general chemistry students solve chemistry problems by recalling facts and algorithms from long-term memory and applying them to the problem at hand . If students have not previously learned these algorithms, problem-solving sessions may not have an immediate positive impact.…”
Section: Limitationsmentioning
confidence: 99%